2011
DOI: 10.1007/s12253-011-9468-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiomatoid Fibrous Histiocytoma: Pleomorphic Variant Associated with Multiplication of EWSR1-CREB1 Fusion Gene

Abstract: Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor which exceptionally occurs in visceral organs or bones. Histologically this is a bland, monomorphic tumor and only occasionally shows pleomorphism. Vast majority of the soft tissue cases share the same translocation and the resulting EWSR1-CREB1 gene fusion as background pathogenetic alteration. Here we report a 10-year-old boy with subcutaneous tumor of the right shoulder. Histological, immunohistochemical and FISH analyses of the case reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The same fusion has been shown in both primary AFH and its nodal metastasis in one case . Multiple EWSR1–CREB1 fusion gene copies have been associated with nuclear pleomorphism . The FUS gene can serve as an alternative 5′ partner with ATF1 .…”
Section: Tumours With Ewsr1–creb1 or Ewsr1–atf1 Fusionssupporting
confidence: 59%
See 2 more Smart Citations
“…The same fusion has been shown in both primary AFH and its nodal metastasis in one case . Multiple EWSR1–CREB1 fusion gene copies have been associated with nuclear pleomorphism . The FUS gene can serve as an alternative 5′ partner with ATF1 .…”
Section: Tumours With Ewsr1–creb1 or Ewsr1–atf1 Fusionssupporting
confidence: 59%
“…Multifocal haemorrhage with blood‐filled cysts is a usual feature. Nuclear pleomorphism and increased mitotic activity are occasionally seen, but do not predict outcome . Extension into deep fascia or muscle has been reported to correlate with local recurrence and distant metastasis .…”
Section: Tumours With Ewsr1–creb1 or Ewsr1–atf1 Fusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of amplification of a fusion gene has been noted in other translocation-associated tumors. 19 , 20 , 21 , 22 Collection and study of additional fibrolamellar carcinomas with amplification of the DNAJB1–PRKACA fusion will be needed to determine the significance of this finding. The second unusual pattern resulted from two genetic events; (i) formation of the fusion gene and (ii) loss of the PRKACA locus on the uninvolved allele.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the diagnosis of AFH in both of these aggressive cases was confirmed by FISH on a molecular level for the presence of rearrangements of both EWSR1 and CREB1. Tamas et al reported that the influence of the EWSR1-CREB1 fusion gene on prognosis was not clear [24]. In the AFH cases in which the EWSR1-CREB1 fusion gene was detected, only one recurrence case was reported [16]; there were no reported deaths.…”
Section: Discussionmentioning
confidence: 99%